Pengaruh Model Pembelajaran Kooperatif Tipe TGT Berbantuan Media Wordwall terhadap Hasil Belajar IPAS Siswa Kelas IV SDN 15 Cakranegara Tahun Ajaran 2025/2026 - Nur Irmayati; Nurwahidah; Vivi Rachmatul Hidayati (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research is based on the low student learning outcomes in science and natural science (IPAS) subjects as well as teacher-centered learning and the lack of use of interactive media in learning. This study aims to determine the effect of the Teams Games Tournament (TGT) cooperative learning model assisted by Wordwall media on the science and natural science (IPAS) learning outcomes of fourth-grade students of Elementary cchool 15 Cakranegara in the 2025/2026 academic year. This study uses a quantitative approach with a quasi-experimental method of the Nonequivalent Control Group Design type. The population consists of all fourth-grade students of of Elementary cchool 15 Cakranegara. The sample was selected using a saturated sampling technique, with Class IVA as the experimental group and Class IVB as the control group. The research instrument was a learning outcome test in the form of multiple-choice questions that measure cognitive indicators of analyzing and evaluating. Data were collected through tests and observations. Observational data were analyzed using descriptive statistics, while learning outcome data were analyzed using n-gain test, prerequisite test, and independent sample t-test for hypothesis testing, with the help of IBM SPSS Statistics 25. The results of hypothesis testing showed a significance value of less than 0.001 < 0.05, which indicated that H₀ was rejected and Hₐ was accepted. In addition, the average posttest score of the experimental group was 83.75, which was higher than the control group, which was 78.91. This indicates that the use of the TGT cooperative learning model assisted by wordwall media has a significant influence on the science learning outcomes of fourth-grade students of of Elementary cchool 15 Cakranegara.